Development of the MY PERPUS Digital Library Website at SMA Muhammadiyah 4 Porong - Muhammad Najih Fairuzzamani; Mochamad Alfan Rosid; Nuril Lutvi Azizah; Ade Eviyanti (Research Parks Publishers, 2026)
The rapid development of information technology has encouraged educational institutions to adopt digital-based systems to improve the effectiveness of administrative management, including school library services. The library of SMA Muhammadiyah 4 Porong still applies a manual system, which causes several problems such as recording errors, difficulties in searching for books, and inefficiency in the borrowing and returning process. This study aims to develop a website-based library information system called MY PERPUS to support library administration and improve service quality. The development method used in this research is the Waterfall model, which consists of requirement analysis, system design, and website development stages. Data were collected through observation and interviews with library staff and visitors. The developed system is equipped with login and registration features, book master data management, borrowing and returning transactions, and book return reminder notifications via Gmail. System testing using the black-box testing method indicates that all features function properly and produce outputs that meet the expected results. Therefore, the MY PERPUS website is able to improve the efficiency of library management, facilitate book searching, and help minimize delays in book returns..